Evaluation of left ventricular functions in patients with retinal vein occlusion - (:unkn) unknown (My University, 2019)
The aim of this study was to evaluate cardiac functions in patients with retinal vein occlusion (RVO) by both conventional and speckle tracking echocardiography (STE). We included 54 consecutive RVO patients, 47 patients with systemic arterial hypertension (SAH), and 52 healthy controls. Two-dimensional echocardiography (2DE) and STE were performed to all patients and healthy subjects in order to assess left ventricle (LV) systolic and diastolic functions. There was no statistically significant differences among-group in clinical data. RVO and hypertensive patients had LV diastolic dysfunction in conventional echocardiographic measurements. The RVO patients had lower LV global longitudinal, radial, circumferential strain measurements than hypertensive patients and healthy controls. LV subclinical dysfunction might be determined by STE in patients with RVO, independent of whether or not they have SAH.